Effective revascularization of non-healing wounds by the human Stromal Vascular Fraction relies on direct cell integration and paracrine signals. (10th June 2022) - Vuerich, R; Groppa, E; Vodret, S; Ring, N; Stocco, C; Bossi, F; Agostinis, C; Colliva, A; Simoncello, F; Benvenuti, F; Agnelli, A; Dore, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): PREFER Introduction: With the increased prevalence of chronic diseases, non-healing wounds place a significant burden on the health system, with a prevalence of 2-5%, similar to the one of heart failure. They are persistent full-thickness skin lesions that affect patients suffering from vascular disorders, such as diabetes and peripheral artery disease. Skin implants and substitutes are currently applied to promote the closure of non-healing wounds. However, both approaches are poorly effective because of lack of appropriate vascularization. Purpose: To promote the neo-vascularization of non-healing wounds, we use Stromal Vascular Fraction (SVF) as innovative therapeutic opportunity for wound treatment. Here, we aim to 1) characterize and demonstrate the pro-angiogenic role of SVF cells and 2) provide pre-clinical evidence of the therapeutic efficacy of the human SVF in promoting the neo-vascularization in a new mouse model of ischemic, non-healing wound. Methods: To assess capacity of SVF-derived cells to improve wound revascularization, we created a new model of non-healing wound generated by wounding an ischemic limb in mice. Human and mouse SVF was purified from adipose tissue and seeded on a clinical-grade skin substitute prior to its implantation on the ischemic wound of a recipient animal. The transplantation of human SVF into NSG immunodeficient mice was verified using species-specific antibodies, while the use of genetically modified mice allowed us to trace the fate of both endothelial and non-endothelial cells upon their transplantation into syngeneic recipient animals. The function of SVF-induced vessels was assessed by systemic injection of biotinylated lectin and by Single Photon Emission Tomography (SPECT) of the treated limb. Results: At day 7 the implanted mouse SVF gives rise to a widespread vascular network composed by arteries, capillaries, veins, as well as lymphatic vessels. Similarly, human SVF-derived endothelial cells formed hybrid human-mouse vessels that were stabilized by perivascular cells. At both histological and functional analysis, these vessels were connected with the host circulatory system and determined a 2-fold increase in tissue perfusion. The comparison of the activity of human SVF from different donors allowed us to disclose its dual mechanisms of action. Conclusions: Here we demonstrated the efficacy of the SVF in promoting neo-vascularization of a skin substitute in a mouse model of ischemic, non-healing wounds. Its therapeutic efficacy relies on dual mechanisms of action. On the one hand, SVF-derived ECs engraft and expand, directly forming new vascular units that colonize the scaffold and extend into surrounding tissues. On the other hand, the mesenchymal progenitors stimulate the expansion of the host vasculature, which extends into the scaffold, with the eventual appearance of donor-host hybrid vessels. Collectively, these data support the use of human SVF as a powerful cell therapy to treat non-healing wounds.